Peningkatan Pemahaman Keagamaan Anak melalui Pendampingan Pembelajaran Praktek Wudhu Anak - Nur Ma’murotun Najah, Evi; Ulya, Himatul; Agustina, Putri Agustina; Salamah, Ummi (LP3M IAIFA Kediri, 2024)
The main aim of this research is to find out the results of the evaluation of the implications of mentoring in learning the practice of ablution at the Al-Firdaus Qur'an Education Park (TPQ), Ngrangkok Hamlet, Klampisan Village by applying the Participatory Action Research (PAR) approach. The selection of this PAR approach hopes for active involvement from all levels of TPQ Al-Firdaus, such as teachers, students, caregivers, and student guardians, in the planning, implementation process, and evaluation of ablution learning to find out the impact of the program. This research strategy involves a process structure consisting of observation, interviews, planning, action, and reflection. Data was collected through interviews, field observations, research team discussions, and documentation. The results of this research show the impact of significant changes both in the level of understanding and skills of the students in carrying out ablution practices by the Shari'ah, and also in strengthening their involvement and support from the TPQ community. Active participation from all interested parties is also very helpful in identifying and alleviating conflicts in the learning process. The conclusion from this research is that the use of the PAR approach is very effective in improving the form of mentoring in religious education which involves all parties involved in the stages of the process. It is hoped that these results can be used as material for consideration for teaching in Islamic educational institutions and can then become a model for other Islamic educational institutions in the future.